Problems of Investor-State Dispute Settlement (ISDS) - KANG, Taewook (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019, 2020)
The research deals with Problems of Investor-State Dispute Settlement (ISDS) focused on Investment Arbitration. The author especially focuses on the problems under BIT (Bilateral Investment Treaties) and FTA (Free Trade Agreements. Mentioned in this article, International investment disputes are generated due to host countries and foreign investors. ISDS is Dispute settlements between investors and countries. This is not suit proceedings but arbitration proceedings. That is, ‘activities of the third party to arbitrate and settle disputes by intervening between parties in dispute. ’However, Dispute Settlement through this way, is it really reasonable and fair system? If it is indeed fair and reasonable system, advanced countries like the United States and Australia would not have abandoned it. Therefore, the investment arbitration system is never a dispute settlement proceeding that has been verified and stabilized internationally.